Lerep Tourism Village in Central Java: Its Basic Tourism Development - Djumiarti, Titik; Purnaweni, Hartuti; Amalia, Sefi; Wulandari, Diah (Indonesian Association for Public Administration (IAPA), 2023)
Tourism is one of the highest factors to encourage economic growth. Tourism development in Indonesia is mostly carried out through the development of tourist villages. Tourism must be designed in order to create a positive impact on society, especially related to economic improvement. One of the Tourism Villages in Central Java is Lerep Village located in West Ungaran district, Semarang Regency which has various agrotourism potentials. This study aims to analyze: